Cretaceous and eocene decapod crustaceans from southern Vancouver Island, British Columbia, Canada - Schweitzer, Carrie E. (Carrie Ellen); Feldmann, Rodney M.; Fam, John; Hessin, William A.; Hetrick, Steven W.; Nyborg, Torrey G.; Ross, Richard L. M. (NRC Research Press, 2003)
A large collection of fossil decapod crustaceans from Cretaceous and Eocene rocks of Vancouver Island, British Columbia, Canada, has yielded a remarkably diverse fauna. The Cretaceous decapod fauna, including previously described and new taxa, contains 17 genera in 14 families, represented by as many as 22 species. The Eocene fauna is less robust, with 7 species and 6 genera in 6 families. This publication includes one new family; three new genera; eight new species; and nine new combinations.